Death Penalty Reform: A Comparative Study of Indonesia’s New Criminal Code and Malaysian Law - Prija Djatmika; Heru Kurniawan (Universitas Negeri Gorontalo, 2026)
This study examines the reform of capital punishment regulation in Indonesia and Malaysia from a human rights perspective. The research aims to analyze the transformation of capital punishment under Law No. 1 of 2023 on the Criminal Code (Indonesia's New Criminal Code) and Malaysia's Abolition of Mandatory Death Penalty Act 2023 (Act 846), as well as to assess their compatibility with international human rights standards. This study employs a normative juridical method using statutory, comparative, and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively through descriptive legal analysis. The findings indicate that both Indonesia and Malaysia have shifted from a rigid retributive model toward a more individualized sentencing framework. Indonesia reclassifies the death penalty as a special and alternative punishment accompanied by a ten-year probationary period, while Malaysia abolishes the mandatory nature of the death penalty by granting judges discretion to impose either capital punishment or long-term imprisonment. Although neither country has abolished the death penalty, both have significantly restricted its application to the most serious crimes, reflecting a middle-ground approach between retentionism and abolitionism. These reforms are generally consistent with Article 6 of the International Covenant on Civil and Political Rights (ICCPR), which permits capital punishment only under strict limitations. Accordingly, the study concludes that the reforms represent a gradual transition toward a more proportionate, human rights-oriented criminal justice system while maintaining capital punishment as an exceptional sanction.